The Struggle Over ‘Surat Ijo’ Land in Surabaya: Legal Mobilization After Reformation - Santoso, Fajar (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2025)
Abstract: This article discusses the dynamics of GERATIS in fighting for the abolition of the Land Use Permit (“Surat Ijo”/IPT) scheme in Surabaya during the period 1970–2010. Using a historical method, this study relies on primary sources such as local regulations, court decisions, National Land Agency documents, and media reports, which are critically analyzed both internally and externally to ensure validity and reduce bias. The findings reveal that the combination of litigation strategies and post-reform mass mobilization successfully introduced new legal discourse regarding the status of the “Surat Ijo,” but its implementation was hindered by organizational fragmentation and resistance from city government policies. This study highlights the limitations of legal victories without comprehensive bureaucratic reform and provides policy recommendations for improving land asset management at the local government level. Keywords: GERATIS, Land, Surat Ijo, Reform